Pilot assessment of patient satisfaction and clinical impact of Medicare Part D in diabetic geriatric patients - Kim SL; Touchette DR; Stubbings JA; Schullo-Feulner AM; Pater KS (Centro de Investigaciones y Publicaciones Farmaceuticas, 2008)
Objectives: To assess patients' 1) satisfaction with their decision to enroll or not enroll in the Medicare Part D program, and 2) clinical status of diabetes before and after decision to enroll in Medicare Part D.Methods: Patients 65 years or older were enrolled in the study from November 2006 through February 2007. Patients were screened by a clinical pharmacist at their clinician visit and administered a Medicare Part D satisfaction survey. Upon completion of the survey, a retrospective chart review was completed in diabetic patients who were enrolled in Medicare Part D to assess goal attainment of glycosylated hemoglobin (HbA1c), low-density lipoprotein (LDL) and blood pressure. Pre-enrollment values were obtained in the 6 months prior to the start of Medicare Part D enrollment (July 1- December 31, 2005). Post-enrollment values were obtained after enrollment was complete for the 2006 year (May 1- October 31, 2006).Results: Results show that 74% (60/81) of patients surveyed were enrolled into the Medicare Part D program, including patients who have dual eligibility. Of the 60 patients who were enrolled in Medicare Part D, 48 patients (80.0%) responded that they were satisfied with their decision to enroll. Clinical outcomes were unchanged from the pre-enrollment to the post-enrollment periods. Mean HbA1c was 7.47% in the pre-enrollment period and 7.25% post-enrollment (differencepre-post = 0.23; 95%CI = -0.28 to 0.73). There was no change in LDL in the two time periods (pre = 79.4 mg/dL; post = 79.7; differencepre-post = -0.25; 95%CI = -13.6 to 13.1). Similarly, there were no significant differences observed for blood pressure. Mean systolic blood pressure was 129.5 in the pre-enrollment period and 131.6 in the post-enrollment period (differencepre-post = -2.1; 95%CI = -7.0 to 2.7). Mean diastolic blood pressure was 70.3 for the pre-enrollment period and 70.7 for the post-enrollment period (differencepre-post = -0.4; 95%CI = -4.2 to 3.4).Conclusion: Patients were generally satisfied with their decision to enroll in Medicare Part D. Clinical outcomes were not affected by participation in a Medicare Part D plan. More longitudinal studies are necessary to determine long term impact of Medicare Part D on diabetes management.